2021
DOI: 10.1186/s12891-021-04133-8
|View full text |Cite
|
Sign up to set email alerts
|

The trochanteric double contour is a valuable landmark for assessing femoral offset underestimation on standard radiographs: a retrospective study

Abstract: Background Inaccurate projection on standard pelvic radiographs leads to the underestimation of femoral offset—a critical determinant of postoperative hip function—during total hip arthroplasty (THA) templating. We noted that the posteromedial facet of the greater trochanter and piriformis fossa form a double contour on radiographs, which may be valuable in determining the risk of underestimating femoral offset. We evaluate whether projection errors can be predicted based on the double contour … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In a cadaveric study performed by Weber et al, 35% of radiographic femoral offset measurements exceeded a 5 mm difference from CT measurements, while leg length and global offset were more reliably within this range, at 1% and 15% respectively [ 15 ]. Blumel et al reported findings that showed a projection error greater than 10% when the distance between radiographic double lines exceeded 5 mm [ 7 ]. This consistent underestimation of femoral offset can exert significant effects on patient outcomes following THA, as decreased postoperative femoral offset negatively affects muscle tensioning, joint stability, implant wear, and leg length perception [ 3 6 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a cadaveric study performed by Weber et al, 35% of radiographic femoral offset measurements exceeded a 5 mm difference from CT measurements, while leg length and global offset were more reliably within this range, at 1% and 15% respectively [ 15 ]. Blumel et al reported findings that showed a projection error greater than 10% when the distance between radiographic double lines exceeded 5 mm [ 7 ]. This consistent underestimation of femoral offset can exert significant effects on patient outcomes following THA, as decreased postoperative femoral offset negatively affects muscle tensioning, joint stability, implant wear, and leg length perception [ 3 6 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative templating via plain radiography is a standard practice to determine prosthetic size and position based on a patient’s native femoral offset, which is defined as the perpendicular distance from the center of rotation of the femoral head to the long axis of the proximal femoral shaft [ 2 ]. Subsequent prosthetic reproduction of femoral offset in THA is important for achieving maximum abductor force and active range of motion and preventing impingement and dislocation [ 3 6 ], and the need to accurately measure femoral offset on plain radiograph has become increasingly recognized in recent years [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All preoperative digital radiographs of the pelvis were taken in an anterior–posterior orientation. Since external rotation of the femur usually leads to underestimation of femoral offset [ 14 ], patients were positioned supine with both hip joints rotated inward by approximately 10–15°. A dual calibration marker ball system (KingMark TM ) was routinely used as a reference for determining the individual magnification factor [ 15 ].…”
Section: Methodsmentioning
confidence: 99%